Internally located and oppositely oriented polymerase II promoters direct convergent transcription of a LINE-like retroelement, the Dictyostelium repetitive element, from Dictyostelium discoideum. - Schumann, G (1994)
The Dictyostelium discoideum NC4 genome harbors approximately 150 individual copies of a retrotransposable element called the Dictyostelium repetitive element (DRE). This element contains nonidentical terminal repeats (TRs) consisting of conserved building blocks A and B in the left TR and B and C in the right TR. Seven different-sized classes of RNA transcripts from these elements were resolved by Northern (RNA) blot analysis, but their combined abundance was very low. When D. discoideum cells were grown in the presence of the respiratory chain blocker antimycin A, steady-state concentrations of these RNA species increased 10- to 20-fold. The D. discoideum genome contains two DRE subtypes, the full-length 5.7-kb DREa and the internally deleted 2.4-kb DREb. Both subtypes are transcribed, as confirmed by analysis of cloned cDNA. Primary transcripts from the sense strand originate at nucleotide +1 and terminate at two dominant sites, located 21 or 28 nucleotides upstream from the 3' end of the elements. The activity of a reasonably strong polymerase II promoter in the 5'-terminal A module is slightly upregulated by the tRNA gene located 50 +/- 4 nucleotides upstream and drastically reduced by the adjacent B module of the DRE. Transcripts from the opposite DNA strand (complementary-sense transcripts) were also detected, directed by an internally located polymerase II promoter residing within the C module. This latter transcription was initiated at multiple sites within the oligo(dA12) stretch which terminates DREs.